Obesity and Lipid Profile Status Amongst the Healthy Physicians Working at a Tertiary Hospital in Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Obesityis closely associated with dysli- pidemia and is now a pandemic of modern world. Both dyslipidemia and obesity are most important cause for the development of major noncommunicable diseases. This study was aimed to assess the pattern of obesity and lipid profile statusamong physicians working at a tertiary levelHospital in Bangladesh.Materials and methods: This descriptive cross-sectional study was doneamong 107 physicians of different departments of Chittagong Medical College Hospital in 2016. Demographic and anthropometric data were collected using a structured case record form. After taking informed written consent, relevant information and physical examination findings were recorded and fasting blood samples were collected to determine the Lipid profile [Total Cholesterol (TC), Triglyceride (TG), Low Density Lipoprotein Cholesterol (LDL-C) and HighDensity Lipoprotein Cholesterol (HDL-C)] of the participant and then results was classified according to National Cholesterol Education Programme Adult Treatment Panel III criteria (NCEP-ATP III).Results: In this study mean age was 32.3±4.5 years with 67.3% in the age group of 31-40 years, and 71% were male. the overall proportion of overweight, obesity, and dyslipidemia were 54.8%, 19.4%, and 81.3%, respectively.  Proportion of male physicians with generalized obesity was significantly higher than female (42.1% versus 19.4%) and reverse trend was observed in the distribution of abdominal obesity, which was higher in female than male (87.1% versus 60.5%). In this lipid profile study most significant abnormality found was low HDL-C (72.9%) followed by elevated TG (57.9%). Respectively, 54.8% and 3% of the female and male physicians have normal lipid profile. In both gender, TC, and TG were positively correlated with BMI and WC. Conclusion: As the burden of obesity and dyslipidemia are high among young physicians, policymakers should consider comprehensive programs for the primary  prevention of CVD among young physicians working at  the tertiary level hospital in Bangladesh.JCMCTA 2023 ; 34 (2) : 3-7